2016
DOI: 10.1002/mame.201500465
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Self‐Etching for Superhydrophobicity through a Green Hot‐Pressing‐Exfoliation Process: Low and High Adhesion

Abstract: A green polymer self‐etching strategy for fabricating superhydrophobic surfaces exhibiting low and high adhesion is proposed by using hot‐pressing and exfoliation on a pair of low density polyethylene (LDPE) films. It is demonstrated that the hot‐pressing temperature has significant influence on the surface morphology of LDPE. Effective hot‐pressing temperature for low‐adhesive superhydrophobicity ranges from 109 to 161 °C. Bird's‐nest like micro‐/nanostructures are observed in the unzipped LDPE surfaces compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Additionally, the surface C/O ratio increased from 1.61 of the pristine string to 2.32 of the treated string, which was attributed to long alkyl chains of grafted HDTMS. For treated strings, low-surface-energy alkyl chains combining with micro/nanoroughness on fiber surfaces benefit the improvement of fiber hydrophobicity [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the surface C/O ratio increased from 1.61 of the pristine string to 2.32 of the treated string, which was attributed to long alkyl chains of grafted HDTMS. For treated strings, low-surface-energy alkyl chains combining with micro/nanoroughness on fiber surfaces benefit the improvement of fiber hydrophobicity [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…Superhydrophobic coatings have been extensively researched and applied in self-cleaning, oil/water separation, anti-condensation, anti-fogging, and anti-icing [ 17 , 18 , 19 , 20 , 21 , 22 ]. Inspired by the lotus leaf effect, numerous studies have shown that superhydrophobicity can be obtained by the combination of micro/nano scale surface roughness and a low-surface-energy coating [ 23 , 24 ]. To endow the fabric with superhydrophobic property, it is usually designed hierarchical roughness on a material possessing low surface energy, or modified a rough surface with a low-surface-energy material [ 25 ].…”
Section: Introductionmentioning
confidence: 99%